2002
DOI: 10.1021/op020221k
|View full text |Cite
|
Sign up to set email alerts
|

Trifluoroacetic Acid-Mediated Cleavage of a Triethylsilyl Protecting Group:  Application in the Final Step of the Semisynthetic Route to Paclitaxel (Taxol)

Abstract: The final step of the semisynthetic route to paclitaxel involves cleavage of the triethylsilyl (TES) protecting group from the C-7 hydroxyl group. Paclitaxel is an extremely complex molecule, and standard deprotection conditions led to formation of several impurities. Trifluoroacetic acid in aqueous acetic acid was found to be very effective in the cleavage of the TES group without compromising the quality of the product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…To test this hypothesis, we examined conditions to convert 1a to its corresponding β-keto ester. Among the desilylation methods attempted, we found TFA in chloroform to be the most effective (eq ), and β-keto ester 4a was isolated in 90% yield by this method. …”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis, we examined conditions to convert 1a to its corresponding β-keto ester. Among the desilylation methods attempted, we found TFA in chloroform to be the most effective (eq ), and β-keto ester 4a was isolated in 90% yield by this method. …”
Section: Resultsmentioning
confidence: 99%
“…Importantly, under these conditions C2‘−OTBS remains intact as confirmed by 1 H NMR analysis (see Supporting Information). Acetic acid has been shown to minimize the formation of side products when used in the synthesis of paclitaxel 1 Synthesis of a Paclitaxel Analogue Featuring a Hexaethylene Glycol Linker at the C-7 Position …”
Section: Resultsmentioning
confidence: 99%
“…The C‐7 epimerization can readily take place in solvent under heating, or under mildly basic conditions such as physiological pH 7, 8. It has been reported that 7‐ epi ‐paclitaxel ( 1b ) and other 7α‐hydroxyltaxanes can be detected from natural sources, in the manufacturing process for paclitaxel‐active pharmaceutical ingredients (APIs), as well as from taxane‐related metabolic samples 3, 9–11. As a common impurity and metabolite of taxane drugs, the monitoring of 1b and other 7α‐hydroxyltaxanes is important for quality control and pharmacological research of taxane drugs.…”
Section: Methodsmentioning
confidence: 99%